Replication Data for: Reducing losses but failing to sequester carbon in soils – the case of Conservation Agriculture and Integrated Soil Fertility Management in the humid tropical agro-ecosystem of Western Kenya - Sommer, Rolf; Paul, Birthe K.; Kihara, Job Maguta; Mukalama, John (International Center for Tropical Agriculture, 2018)
Soil organic carbon content of topsoil (0-15 cm depths) of two agronomic long-term trial (CT1 and INM3), collected repeatedly throughout the years